THE NATIONAL MARITIME AUTHORITY AND ITS RESOURCES AGAINST ILLICIT DRUG TRAFFICKING - Champa Sánchez, José Antonio (2022)
This article addressed the resources of the National Maritime Authority against illicit drug trafficking by sea in the port of Callao, the objective was to determine how the resources of the National Maritime Authority were effective in the fight against drug trafficking. drug trafficking in the port of Callao. The research methodology was framed in the qualitative approach, using techniques for collecting information such as observation, interviews and documentary analysis and for the analysis of the results obtained, it was carried out through a narrative description of the data obtained, the triangulation of data for each technique, to conclude with a comprehensive results triangulation matrix, which concluded it was possible to determine that it is necessary to give greater power of action, providing the necessary economic resources, and for this it must be included in the National Strategy to Fight against Drugs from 2022-2026, the granting of a budget project for the permanent control of the exit of drugs abroad, which would also reinforce the work of maritime patrol in a repetitive manner, the acquisition and use of radars and equipment of high technology, as well as the reinforcement of the Intelligence Directorate for a coordinated work between the various national and international port captaincies.